Pengaruh Religiusitas Diri dan Orangtua terhadap Kebahagiaan Remaja - Rini Rini (Universitas Persada Indonesia YAI, 2023)
Religiosity has an important role in shaping teenage happiness. Belief in God can bringpeace that brings happiness. In addition, having parents who are also religious can maketeenagers feel more calm in parenting and feel happy. This study has two objectives, todetermine the effect of religiosity on teenage happiness and the influence of parentalreligiosity on teenage happiness. The respondents of this study were 464 teenagers, withaccidental sampling technique. Data is collected by google forms which are distributed viaWhatsApp, Telegram, Facebook, and email. Data analysis using linear regression. Theresults showed that religiosity positively influenced and significantly related to teenagehappiness, and parental religiosity positively influenced and significantly related toteenage happiness. Also, parental religiosity positively influenced and significantly relatedto teenager religiosity.